Strategy for Implementing Agricultural Extension Methods and Materials in the New Normal Era in Serang Regency, Banten Province - Asep Supriatna (Jurnal Multidisiplin Madani, 2022)
President Joko Widodo on March 24 2020, stated that even in a pandemic situation, the economic sector including agriculture must continue to move and produce by observing health protocols. The purpose of this study was to find out the strategy for implementing extension methods and agricultural extension materials that are in accordance with the new normal era in Serang Regency, in terms of technical, economic and social institutional aspects, as well as linking audience characteristics to the discussion, both on farm and off farm segments; to determine the appropriate agricultural extension model, and to determine the priority scale of the elements analyzed; The research method used is a mixed method, which combines descriptive-exploratory methods with the Analytical Hierarchy Process, supported by 37 participants located in Serang Regency. Based on the results of the analysis, the strategy for implementing extension methods and agricultural extension materials in the new normal era in Serang Regency, the priority criteria are on the technical aspect, and in terms of indicators, the material indicators are the main priority, followed by the second priority, namely the extension method indicator